Changes in the Blood-Brain Barrier Function Are Associated With Hippocampal Neuron Death in a Kainic Acid Mouse Model of Epilepsy - Yan, Bing Chun; Xu, Pei; Gao, Manman; Wang, Jie; Jiang, Dan; Zhu, Xiaolu; Won, Moo-Ho; Su, Pei Qing (Frontiers in Neurology, 2018)
The kainic acid (KA)-induced epilepsy experimental model is widely used to study the mechanisms underlying this disorder. Recently, the blood-brain barrier (BBB) has become an innovative alternative treatment target for epilepsy patients. KA causes neuronal injury and BBB damage in this experimental epilepsy model but the mechanisms underlying epilepsy-related neuronal injury, autophagy, and BBB damage remain unclear. Therefore, the present study investigated the relationships among neuronal injury, the expressions of autophagy-related proteins, and changes in BBB-related proteins during the acute phase of epilepsy to further understand the mechanisms and pharmacotherapy of epilepsy. NeuN immunohistochemistry and Fluoro-Jade B (FJ-B) staining in the hippocampal CA3 region revealed that neuronal death induced by intraventricular injections of 10 μg/kg KA was greater than that induced by 3 μg/kg KA. In addition, there were transient increases in the levels of microtubule-associated protein light chain 3-II (LC3I/II) and Beclin-1, which are autophagy-related proteins involved in neuronal death, in this region 24 h after the administration of 10 μg/kg KA. There were also morphological changes in BBB-related cells such as astrocytes, endothelial cells (ECs), and tight junctions (TJs). More specifically, there was a significant increase in the activation of astrocytes 72 h after the administration of 10 μg/kg KA as well as continuous increases in the expressions of platelet endothelial cell adhesion molecule-1 (PECAM-1) and BBB-related TJ proteins (Zonula occludens-1 and Claudin-5) until 72 h after KA treatment. These results suggest that the overexpression of autophagy-related proteins and astrocytes and transient increases in the expressions of BBB-related TJ proteins may be closely related to autophagic neuronal injury. These findings provide a basis for the identification of novel therapeutic targets for patients with epilepsy.